An Analysis of EFL Junior Secondary School Students’ Motivation in Vocabulary Learning Through Quizizz - Murdia Murdia; Sukmawati Sukmawati; Mansyur Mansyur (INSIGHT: Indonesian Journal Social Studies and Humanities, 2026)
Abstrak. This research aimed to analyze the levels of junior secondary school students’ intrinsic and extrinsic motivation in English vocabulary learning using Quizizz. It was conducted among grade 8 students at SMP Negeri 4 Mambi, Mamasa Regency, West Sulawesi province, in the 2025/2026 academic year. A mixed method approach was employed in this study. To gather the data, an online questionnaire and semi-structured interviews were used. The total participants were 31 students, who filled out the online questionnaires and 5 of them were chosen purposely that were consented to be interviewed. The data were analyzed quantitively and qualitatively. Those listed statements in the questionnaires were validated through Self-Determination Theory before they were administered to the observed group. The findings showed that the level of intrinsic motivation was at a high degree level, which had a total mean score 3.72, while the extrinsic motivation level of students was at 3.69, indicating that the level was also high. These results were further confirmed through in-depth interviews with students, where they were highly motivated and engaged in English vocabulary learning by using Quizizz as an interactive digital learning application in the classroom due to its interactive, score and feedback features in the application. The future researchers may investigate the impact of such application on other language skills, its effectiveness at various proficiency levels, and the implementation in long – term duration. Keywords: EFL Students’ Motivation, English Vocabulary Learning, Quizizz